2002
DOI: 10.2337/diabetes.51.7.2190
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Glycogen Synthase Kinase 3 Improves Insulin Action and Glucose Metabolism in Human Skeletal Muscle

Abstract: Glycogen synthase kinase (GSK)-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
144
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(153 citation statements)
references
References 60 publications
6
144
1
2
Order By: Relevance
“…It was first demonstrated that sites 3a and 3b were phosphorylated by the protein kinase GSK-3 (11)(12)(13). Studies with cells and with animals have also shown that known inhibitors of GSK-3 can affect glycogen synthesis (26,27). However, more recent studies indicated that alternative pathway(s) for the phosphorylation of these sites in glycogen synthase may operate (10,18).…”
Section: Discussionmentioning
confidence: 99%
“…It was first demonstrated that sites 3a and 3b were phosphorylated by the protein kinase GSK-3 (11)(12)(13). Studies with cells and with animals have also shown that known inhibitors of GSK-3 can affect glycogen synthesis (26,27). However, more recent studies indicated that alternative pathway(s) for the phosphorylation of these sites in glycogen synthase may operate (10,18).…”
Section: Discussionmentioning
confidence: 99%
“…In one of the few reports, Nikoulina et al (37) found that inhibition of GSK-3 for 4 days increased both basal and insulin-stimulated glucose uptake in skeletal muscle without changing expression of either GLUT1 or GLUT4. Similarly, Bentley et al (4) showed that IL-3 stimulated translocation of GLUT1 to the cell surface of mast cells, and Wieman et al (42) found that this IL-3 effect on Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GSK-3 is known to function downstream of phosphatidylinositol 3-kinase (PI3K) and Akt (41). There is a paucity of reports about regulation of GLUT1 mediated glucose uptake by GSK-3, and the few studies that have been performed have produced different findings in different cell systems (37,42).…”
mentioning
confidence: 99%
“…5A). We surmised that this protein could be Gsk-3␤ on the basis of the molecular weight and its known involvement in the regulation of glucose metabolism (44). Phosphorylation of Gsk-3␤ Ser-9, the Akt-dependent phosphorylation site in Gsk-3␤, increased significantly in Irs-1 Ϫ/Ϫ /Irs-2 Ϫ/Ϫ cells expressing WT Irs-2 relative to vector controls, and this increase was not observed in the same cells expressing Irs-2 Y5F (Fig.…”
Section: Irs-2mentioning
confidence: 99%